Unravelling the influence of cluster thinning on wine quality: a narrative systematic review - Cassie Marbach; Charlie Hall; Andreea Botezatu (OENO One)
This review examines the impact of cluster thinning (CT) on wine quality. CT is a vineyard management technique intended to enhance the sensory attributes of wine, such as aroma and flavour. We employed a narrative approach, synthesising findings from various studies without the use of statistical meta-analysis. This method allowed us to capture a broad spectrum of insights and draw practical conclusions for winemakers. Our review spans different grape varieties and climates. The studies reviewed include CT interventions at various growth stages—flowering, fruit set, veraison, and post-veraison—with varying levels of thinning severity. Methods range from manual thinning to mechanical approaches, with comparisons made to control groups that did not undergo CT. Our primary focus was on sensory analysis, wine phenolic composition volatile compound composition, and overall quality assessments. We paid particular attention to sensory descriptors related to aroma and flavour profiles, evaluating quality and preference scores. This review consolidates existing research to provide a comprehensive understanding of CT's role in viticulture. It offers practical guidance for optimising CT practices to improve wine quality and identifies areas where further research is needed. By integrating diverse findings, this review contributes valuable insights for winemakers aiming to enhance their vineyard management techniques.